The impact of different data sources on the level and structure of income inequality - Luis Ayala; Ana Pérez; Mercedes Prieto Alaiz (SERIEs - Journal of the Spanish Economic Association, 2022)
This paper aims to analyze the effect on measured inequality and its structure of using administrative data instead of survey data. Different analyses are carried out based on the Spanish Survey on Income and Living Conditions (ECV) that continued to ask households for their income despite assigning their income data as provided by the Tax Agency and the Social Security Administration. Our main finding is that the largest discrepancies between administrative and survey data are in the tails of the distribution. In addition to that, there are clear differences in the level and structure of inequality across data sources. These differences matter, and our results should be a wake-up call to interpret the results based on only one source of income data with caution.
Keywords: D31; D63; 330; Administrative data; Copula; Dependences; Inequality; Measurement error